Latent profile analysis of rehabilitation motivation in Chinese patients with stroke: a cross-sectional study - Tang, Rong; Sun, Qiuxue; Li, Juan; Jiang, Xiaowen; Liu, Shuxian; Chen, Xi; Lv, Yumei (Frontiers in Psychology, 2025)
ObjectiveThis study used latent profile analysis to identify distinct profiles of rehabilitation motivation among Chinese patients with stroke and explored the multidimensional predictors of rehabilitation motivation across different patient subgroups based on the biopsychosocial medical model.MethodsFrom September 2024 to January 2025, 328 patients with stroke were recruited from the rehabilitation departments of three tertiary hospitals in China using convenience sampling. Data collection included (1) a general information questionnaire, (2) Chinese version of the Stroke Rehabilitation Motivation Scale, (3) Modified Barthel Index, (4) the National Institutes of Health Stroke Scale, and (5) Kessler Psychological Distress Scale. Data were analyzed using Mplus version 8.3 and SPSS version 27.0.ResultsThree latent classes of rehabilitation motivation were identified among patients with stroke: (1) Low Rehabilitation Motivation-Intrinsic Drive Deficiency (Class 1, 30.2%), (2) Moderate Rehabilitation Motivation-Extrinsic Drive Stability (Class 2, 39.0%), and (3) High Rehabilitation Motivation-Intrinsic Drive Sufficiency (Class 3, 30.8%). Multiple logistic regression indicated that age, monthly household income, ADL, severity of neurological impairment, and psychological distress were significant predictors of different rehabilitation motivation classes.ConclusionThis study identified significant heterogeneity in the rehabilitation motivation profiles of patients with stroke. Healthcare professionals should implement targeted interventions based on the distinct motivational profiles of patients with stroke during their rehabilitation process, with the aim of effectively mobilizing their intrinsic motivation to participate in rehabilitation therapy.